Improving diagnostic efficacy of primary prostate cancer with combined 99mTc-PSMA SPECT/CT and multiparametric-MRI and quantitative parameters - Zhang, Yu; Shi, Yuanying; Ye, Liefu; Li, Tao; Wei, Yongbao; Lin, Zhiyi; Chen, Wenxin (Frontiers in Oncology, 2023)
Purpose: This prospective study aimed to evaluate the difference between 99m Tc-PSMA single-photon emission computed tomography (SPECT)/CT and multiparametric magnetic resonance imaging (mpMRI) in the detection of primary prostate cancer (PCa).Fifty-six men with suspected PCa between October 2019 and November 2022 were prospectively enrolled in this study. The median age of the patients was 70 years (range, 29-87 years). Patients were divided into high-(Gleason score ＞ 7, n=31) , medium-(Gleason score=7, n=6) and low-risk groups (Gleason score < 7, n=6). All patients underwent 99m Tc-PSMA SPECT/CT and mpMRI at an average interval of 3 days (range, 1-7 days). The maximum standardized uptake value (SUVmax), the minimum apparent diffusion coefficient (ADCmin), and their ratio (SUVmax/ADCmin) were used as imaging parameters to distinguish benign from malignant prostatic lesions.Results: Of the 56 patients, 12 were pathologically diagnosed with a benign disease, and 44 were diagnosed with PCa. 99m Tc-PSMA SPECT/CT and mpMRI showed no significant difference in the detection of primary PCa (kappa =0.401, P=0.002), with sensitivities of 97.7% (43/44) and 90.9% (40/44), specificities of 75.0% (9/12) and 75.0% (9/12), and AUC of 97.4% and 95.1%, respectively. The AUC of SUVmax/ADCmin was better than those of SUVmax or ADCmin alone. When ≥ 删除[Microsoft Office User]: 37 删除[Microsoft Office User]: medium-删除[Microsoft Office User]: high-(Gleason score≥7) and medium-low-risk groups (Gleason score <7) 删除[Microsoft Office User]:SUVmax/ADCmin in the prostatic lesion was >7.0×10 3 , the lesion was more likely to be malignant. When SUVmax/ADCmin in the prostatic lesion is >27.0×10 3 , the PCa patient may have lymph node and bone metastases. SUVmax was positively correlated with the Gleason score (r=0.61, P=0.008), whereas ADCmin was negatively correlated with the Gleason score (r=-0.35, P=0.023). SUVmax/ADCmin was positively correlated with the Gleason score (r=0.59, P=0.023). SUVmax/ADCmin was the main predictor of the high-risk group, with an optimal cut-off value of 15.0×10 3 .The combination of 99m Tc-PSMA SPECT/CT and mpMRI can improve the diagnostic efficacy for PCa compared with either modality alone; SUVmax/ADCmin is a valuable differential diagnostic imaging parameter.